The Investigation of Specific Words Related to the English, German and French Languages in the Explanatory Dictionary of the Uzbek Language (Texas Journal of Philology, Culture and History, 2022)
The article discusses the study of specific words which are related to the English, German and French languages. In addition, it deals with the problems of borrowing words which are based on different spheres of linguistics.